2021
DOI: 10.21547/jss.817480
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Process and Human Rights Developments in the MENA Region: The Cases of Egypt and Tunisia

Abstract: Orta Doğu ve Kuzey Afrika'daki ayaklanmalardan on yıl sonra, geçiş süreci belirsizliğini korumaktadır ve bölgedeki geçiş ülkeleri insan hakları uygulamalarının iyileştirilmesi konusunda birçok zorlukla karşı karşıya bulunmaktadır. Bu makale, Orta Doğu ve Kuzey Afrika Bölgesindeki 2011 ayaklanmalarından sonra insan haklarının gelişimine bakacak ve insan haklarının iyileştirilmesi vaadini taşıyan geçiş sürecinin neden başarısız olduğu sorusuna cevap vermeye çalışacaktır. 2011 ayaklanmalarından sonra Mısır ve Tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, Kolusayın et al (2015) found that 80.4% of the respondents did not receive any training on the handling of biological evidence, underscoring an urgent unmet need in this field. In a study of nurses working in the ED of military hospitals operated by the Turkish Armed Forces, Saral (2008) found 86.5% and 95.4% reported receiving no education or training on forensic nursing as part of their vocational training and postgraduate education, respectively, whereas 64.4% of these nurses did not receive any in-service training. Similarly, Bahar found 97.1% of the 35 nurses studied did not receive any education or training on forensic nursing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kolusayın et al (2015) found that 80.4% of the respondents did not receive any training on the handling of biological evidence, underscoring an urgent unmet need in this field. In a study of nurses working in the ED of military hospitals operated by the Turkish Armed Forces, Saral (2008) found 86.5% and 95.4% reported receiving no education or training on forensic nursing as part of their vocational training and postgraduate education, respectively, whereas 64.4% of these nurses did not receive any in-service training. Similarly, Bahar found 97.1% of the 35 nurses studied did not receive any education or training on forensic nursing.…”
Section: Discussionmentioning
confidence: 99%
“…In general, nurses routinely examine patients at the time of hospital admission—identifying complaints, tailoring and employing management strategies, and evaluating and reporting the outcomes. In forensic cases, they are also responsible specifically for collecting, protecting, and preserving, and transferring evidence to the legal authorities (Bahar, 2008; Pınar & Bahar, 2011; Saral, 2008). When nurses are not equipped with necessary education in forensic nursing, they may make mistakes, such as the nonlabeling or mislabeling of patient samples; take inadequate samples; transfer samples without the use of the correct chemical preservatives; use the preservatives inaccurately; damage samples because of inappropriate packaging; and disrupt the evidence delivery chain because of mistakes in the registration of biological material (Demircan et al, 2008; İnanır et al, 2009).…”
Section: Discussionmentioning
confidence: 99%